Associação da infecção por citomegalovírus e estenose biliar em pacientes submetidos a transplante hepático - Juliano Félix Castro (2020)
INTRODUCTION: Liver transplantation is the treatment of choice for end-liver stage disease. Despite technical advances, transplantation still faces complications that impact patients' survival and quality of life. Among post-transplant complications, biliary strictures and infectious complications are the most frequent. Biliary strictures are classified as anastomotic and non-anastomotic. Several factors are related to the appearance of biliary strictures, such as CMV infection, prolonged cold ischemia time, donor age, MELD, among others. OBJECTIVES: To evaluate the association of cytomegalovirus infection, as well as its prevalence in the development of biliary stenosis in patients undergoing liver transplantation. METHODS: Retrospective cohort study of 175 patients undergoing liver transplantation at the Felicio Rocho Hospital from January 2011 to September 2017. RESULTS: 201 patients were transplanted at the Felicio Rocho Hospital from January 2011 to September 2017. Among these, 175 were included in this study. The average age of the recipients was 54 years, 129/175 (73.7%) were male. 21/175 (12%) developed biliary complications and 9/175 (5.1%) had more than one complication. The main biliary complication was stenosis (9.1%), followed by cholangitis, fistula (2.8%) and calculus (2.2%). Among the biliary complications 16/21 (76%) patients developed stenosis, 14/16 (87.5%) of the anastomotic type and 02/16 (12.5%) of the non-anastomotic type. CMV infection was confirmed in 40/175 (22.9%) patients. Among CMV positive patients, 2/40 patients (5%) developed biliary complications after the diagnosis of CMV. In the univariate analysis, the presence of previous CMV was associated with the development of biliary complications (p = 0.014), as well as stenosis (p = 0.008). However, in the multivariate assessment there was no significance, as well as the type of stenosis. The average MELD in the group of patients who developed biliary stenosis was 21, while the average MELD in the group of patients who did not develop was 17 (p = 0.033). Among the other factors evaluated (Age of the donor, Age of the recipient, sodium donor, CIT, thrombosis of the artery and MELD), only MELD> 21 presented itself as an independent risk factor for the development of biliary complications (p = 0.013) and biliary stenosis (p = 0.019) in the multivariate analysis. CONCLUSION: CMV infection was not associated with the development of post-transplant non-anastomotic biliary stenosis. However, the presence of CMV, as well as MELD> 21, were a risk factor for the development of biliary complications and biliary stenosis in univariate analysis. Only MELD> 21 showed significance for the appearance of biliary complications and stenosis in the multivariate analysis.